Pengaruh Literasi Keuangan Syariah terhadap Perilaku Keuangan Masyarakat Binaan Pondok Pesantren Daarut Tauhid Kabupaten Bogor - F. B. Ramdhani; M. Y. Ibrahim; M. F. Bin Masruhen; N. Fhadiyah (Prodi Ekonomi Syariah, Fakultas Syariah, Institut PTIQ Jakarta, 2022)
The issue of sharia financial literacy is closely related to one's ability to know and understand Islamic financial products and services based on sharia principles. The purpose of sharia financial literacy is expected not only to know and understand sharia financial services institutions and sharia financial products and services but also how to be able to change and improve people's behavior in sharia financial management so as to improve public welfare. This study aims to analyze the level of Shariah financial literacy and the influence of the level of sharia financial literacy on the financial behavior of the people guided by the Daarut Tauhid Islamic Boarding School in Bogor. Data analysis uses descriptive statistical analysis and multiple linear regression analysis. Cumulatively, all sharia financial literacy variables have a positive effect on people's financial behavior. Partially, each variable has a positive effect.